White Material: Ivory tiles, white womanhood, and white supremacy in Jean-Marc Vallée's Sharp Objects. Issue 1 (February 2023) - Sanders, Emily
Abstract : Jean-Marc Vallée's HBO miniseries, Sharp Objects (2018), follows Camille Preaker (Amy Adams) as she returns to her childhood home in Wind Gap, Missouri, to investigate the murders of two young girls. This article explores a specific type of object related to the systems of violence that reveal themselves over the course of the miniseries: ivory tiles. Here, the ivory tiles affixed to the floor of Camille's mother's, Adora Crellin's (Patricia Clarkson), master bedroom both reveal and influence sinister behaviours of the household's women. In employing concepts inspired from Thing Theory and Object-Oriented Ontology, as well as critical theory, this article examines how the ivory tiles possess multilayered excesses that constitute an object's thingness. The foremost excess that informs the ivory tiles' thingness, I contend, is its relationship to white supremacy. It is not only the tiles' material history that informs its relationship to white supremacy, but how, through outlining the forms of agency things possess under Thing Theory, the tiles are able to reveal the forms of violence that are structured within the domestic sphere of the Crellin home. A product of violence, the ivory tiles as things speak back to the design of white supremacy.